2011
DOI: 10.1021/jm1014605
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of a Series of Benzothiazole Phosphoinositide 3-Kinase (PI3K)/Mammalian Target of Rapamycin (mTOR) Dual Inhibitors

Abstract: Phosphoinositide 3-kinase α (PI3Kα) is a lipid kinase that plays a key regulatory role in several cellular processes. The mutation or amplification of this kinase in humans has been implicated in the growth of multiple tumor types. Consequently, PI3Kα has become a target of intense research for drug discovery. Our studies began with the identification of benzothiazole compound 1 from a high throughput screen. Extensive SAR studies led to the discovery of sulfonamide 45 as an early lead, based on its in vitro c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 58 publications
0
60
0
1
Order By: Relevance
“…Angelo et al [90] identified benzothiazole compound 265 (PI3Kα Ki = 53 nM, mTOR Ki > 25 μM) as an initial hit from HTS, and the crystal structure suggested that the ribose pocket might accommodate larger groups than pyrimidine. Extensive SAR studies, including the link atom (sulfur, oxygen and nitrogen) and the pyridine replacing pyrimidine (266-268), led to the sulfonamide 269 (PI3Kα Ki = 38 nM, mTOR Ki = 269 nM) for as an early lead, with high in vitro and in vivo clearance.…”
Section: Pyridines Quinolines Indoles and Indazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…Angelo et al [90] identified benzothiazole compound 265 (PI3Kα Ki = 53 nM, mTOR Ki > 25 μM) as an initial hit from HTS, and the crystal structure suggested that the ribose pocket might accommodate larger groups than pyrimidine. Extensive SAR studies, including the link atom (sulfur, oxygen and nitrogen) and the pyridine replacing pyrimidine (266-268), led to the sulfonamide 269 (PI3Kα Ki = 38 nM, mTOR Ki = 269 nM) for as an early lead, with high in vitro and in vivo clearance.…”
Section: Pyridines Quinolines Indoles and Indazolesmentioning
confidence: 99%
“…In previous studies, Wurz et al [90] disclosed sulfonamide benzothiazole derivatives (e.g. 366, PI3Kα Ki = 1.2 nM, mTOR IC 50 = 2.1 nM) as potent PI3K/mTOR dual inhibitor, while had low solubility.…”
Section: Pyridines Quinolines Indoles and Indazolesmentioning
confidence: 99%
“…Many of the recently reported potential drug candidates [224][225][226][227] and natural products were synthesized by using a Negishi cross-coupling as one of the key steps in the total synthesis. Some of the representative structures of biologically active compounds are shown in Table 3.15.…”
Section: Bibenzyls Homoallylarenes 15-dienes Homopropargylarenesmentioning
confidence: 99%
“…With substantial structural and biochemical information of PI3K inhibitors available, we searched a number of X-ray co-crystal structures of PI3K subunits bound to small molecule inhibitors and explored the binding modes at the ATP-binding site. [20,[28][29][30][31] The active sites of PI3K subunits were mainly comprised of three key regions: the hinge binder, the affinity pocket 3L08). (C) Sequence alignment between PI3Kα, β, γ and δ.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][34][35][36][37][38][39][40][41] Crystallographic analysis found that this scaffold fits the active site very well and thus possesses a high ligand efficiency (LE). As shown in Figure 2(B), the quinoline nitrogen forms a hydrogen bond interaction with Val882 (Val851 in PI3Kα) in the hinge binder region of the kinase domain of PI3Kγ.…”
Section: Introductionmentioning
confidence: 99%